Inovasi Pelayanan Kesehatan Mobile JKN Di Kantor BPJS Kota Subulussalam - Reviana Br Sagala; Vellayati Hajad (Journal of Social Politics and Governance (JSPG), 2022)
This paper discusses health service innovations at the Subulussalam City BPJS Office. The purpose of this study is to see how the development of BPJS Health innovations can provide good services for the community through the Mobile JKN application. This study uses a qualitative research method with a case study approach to see the development of Mobile JKN innovations. Data collection techniques through interviews with BPJS staff and the community using Mobile JKN. The results show that Mobile JKN has developed well because it has complete features and can be used anywhere and anytime so that health services can be more effective and efficient. The conclusion of this study is that health service innovation through Mobile JKN is good, it can be seen through three indicators, namely, good quality, has a variety of functions and the Mobile JKN application also has a uniqueness that is different from other applications.